Filtering by movement in visual search. - McLeod, P; Driver, J; Dienes, Z; Crisp, J (1991)
Search for a target defined by a conjunction of movement and form (e.g., an X moving up in a display of intermingled Os moving up and stationary Xs) is parallel. This result is also found if (a) the moving Os and target X move in unpredictable directions so that the moving stimuli do not form a clear perceptual group or (b) the nontarget Xs also move but in a known, different direction from the Os and target X. In contrast, search is slow and serial if the target may be unpredictably among either moving or stationary stimuli. These results suggest that a component of the visual system operates as a movement filter that can direct attention to stimuli with a common movement characteristic. The filtering cue can be moving (vs. stationary), or movement in 1 particular direction. The results do not support the view that attention can only be directed to groups defined by common fate.